Principle of Strict Liability in Narcotics Crimes and Efforts to Protect The Rights of Perpetrators - Cony Dehas Ratna Devi; Yaris Adhial Fajrin; Syariful Alam; Yohana Puspitasari Wardoyo (SALAM: Jurnal Sosial dan Budaya Syar-i, 2021)
Narcotics abuse cases in Indonesia have been at an alarming level, which causes all levels of society to become targets of victims of narcotics abuse. Efforts to overcome this use two approaches in the narcotics law that regulate it, namely the penal approach and the non-penal approach, which are commonly referred to as the double-track system. As a form of transnational organized crime, narcotics crimes need special efforts to overcome them. Among the many substances of criminal legislation, one of the special measures that can be used is applying the benefits of the existence of the principle of strict liability. The discussion regarding the existence of the principle of strict liability will be the object of study in this paper, namely by using the normative legal research method which prioritizes the study of positive legal provisions and general legal principles. So, it can be found what the strict liability principle is in the teachings of criminal law and the use of the strict liability principle in enforcing criminal law in the field of narcotics in Indonesia. The principle of strict liability can be an option for a new breakthrough in the effectiveness and efficiency of combating narcotics crimes in Indonesia. Although the existence of the principle of strict liability in its implementation provides convenience and practicality for law enforcement officials in carrying out their duties, it also provides an opportunity for injustice. So that the focus of the application of the principle of strict liability is not only used as a means of making it easier but is more used to overcome injustice for the victim or the perpetrator in cases of narcotics abuse so that it will no longer cause an injustice that can injure the basic human rights contained in the paragraph 1 Article 28D of the Indonesia Constitution.Keywords: Narcotics, strict liability, transnational organized crime. Abstrak:Kasus penyalahgunaan narkotika di Indonesia sudah berada pada level yang mengkhawatirkan, yang menyebabkan semua lapisan masyarakat menjadi sasaran korban penyalahgunaan narkotika. Upaya penanggulangannya menggunakan dua pendekatan dalam undang-undang narkotika yang mengaturnya, yaitu pendekatan penal dan pendekatan non penal yang biasa disebut dengan sistem jalur ganda. Sebagai salah satu bentuk kejahatan transnasional terorganisir, kejahatan narkotika memerlukan upaya khusus untuk menanggulanginya. Di antara sekian banyak substansi peraturan perundang-undangan pidana, salah satu upaya khusus yang dapat digunakan adalah dengan menerapkan manfaat dari adanya prinsip pertanggungjawaban yang tegas. Pembahasan mengenai adanya asas strict liability akan menjadi objek kajian dalam tulisan ini, yaitu dengan menggunakan metode penelitian hukum normatif yang mengutamakan kajian ketentuan hukum positif dan asas hukum umum. Sehingga dapat diketahui apa prinsip strict liability dalam ajaran hukum pidana dan penggunaan prinsip strict liability dalam penegakan hukum pidana di bidang narkotika di Indonesia. Prinsip strict liability dapat menjadi pilihan terobosan baru dalam efektivitas dan efisiensi pemberantasan tindak pidana narkotika di Indonesia. Meskipun adanya prinsip strict liability dalam pelaksanaannya memberikan kemudahan dan kepraktisan bagi aparat penegak hukum dalam menjalankan tugasnya, namun juga memberikan peluang terjadinya ketidakadilan. Sehingga fokus penerapan prinsip strict liability tidak hanya digunakan sebagai sarana untuk mempermudah tetapi lebih banyak digunakan untuk mengatasi ketidakadilan bagi korban atau pelaku dalam kasus penyalahgunaan narkotika sehingga tidak lagi menimbulkan kerugian. ketidakadilan yang dapat mencederai hak asasi manusia yang terkandung dalam ayat 1 Pasal 28D Undang-Undang Dasar Negara Republik Indonesia.Kata Kunci: Narkotika; Strict Liability; Kejahatan Terorganisir Transnasional.